Feeding and Growth in the Ephyra Stage of Aurelia coerulea: An In Situ Study - Seo Yeol Choi; Kyoung Yeon Kim; Seok Hyun Youn (Biology, 2025)
The ecological role and in situ feeding potential of Aurelia coerulea ephyrae remain poorly quantified. We conducted in situ chamber experiments in Geoje and Jaran Bay, Korea, to evaluate clearance rates, specific growth rate (SGR), and grazing carbon among ephyrae of different sizes and origins. Larger field-collected ephyrae had higher clearance rates (4.2 ± 0.8 mL ind−1 h−1) and grazing carbon (17.2 ± 1.0 μg C ind−1 d−1) than smaller individuals (1.6 ± 0.5 mL ind−1 h−1; 5.2 ± 1.1 μg C ind−1 d−1), though the differences were not statistically significant (p > 0.05). Field-collected ephyrae exhibited significantly greater clearance (p < 0.05) and grazing carbon (p < 0.01) than laboratory-reared ephyrae, while laboratory-reared ephyrae had higher SGR (p < 0.01).Grazing efficiency did not differ significantly between groups (p > 0.05). SGR peaked at intermediate prey concentrations (0.189 ± 0.013 d−1, p < 0.05), with reduced growth at both lower and higher concentrations. These results indicate that in situ feeding and growth rates are lower than laboratory rates, and that early-stage predation by ephyrae is modulated by prey availability and environmental history. Such findings provide essential baseline data for predicting the bloom dynamics and ecological impacts of Aurelia in temperate coastal environments.